Motivations for Smoking Among Hungarian Police Students - Erdős, Ákos (European Journal of Mental Health, 2023)
Introduction: Police officers’ job is one of the most stressful professions. Job stress, unpredictability, and physical strain can increase the prevalence of smoking among police officers. Investigating the motivations behind smoking stands, therefore, as a critical question, especially in high-risk populations, like police officers. Aims: The aim of the study was to investigate the smoking motivations of Hungarian police students. Methods: Employing a cross-sectional approach, we conducted a questionnaire- based survey among Hungarian police students between January and April, 2022. The study sample (N = 270) consisted of 57.4% male (n = 155) and the average age of students was 21.8 years (SD = 2.13). The survey examined smoking status, frequency and intensity of smoking. Smoking intensity is generally based on self-reported average cigarettes per day. The Substance Use Coping Inventory (SUI) was used to examine motivational attitudes. Results: The lifetime prevalence of smoking among police students reached 77.0%. Female police students were more likely to have tried smoking than males, however, the difference was not significant (p = .114). Among current smokers, male police students demonstrated higher scores than female police students in both the self-confidence motives (p = .009) and boredom relief motives (p = .010). When comparing regular and occasional smokers, we found significant differences in all motivational scales, except for social motivators. However, logistic regression results indicate that boredom relief motives are the only significant predictors of regular smoking among police students (OR = 1.45; p < .001). Conclusions: The motivational patterns of smoking vary between males and females, as well as between regular and occasional smoker police students. A pivotal inquiry in the context of preventing regular smoking among police students revolves around identifying alternative solutions to effectively occupy their leisure time and alleviate boredom.